2021
DOI: 10.3389/fphys.2021.790034
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of a Minimal Dose Eccentric Resistance Training Paradigm to Combat Sarcopenia and Age-Related Muscle and Physical Function Deficits in Older Adults

Abstract: The ability of older adults to perform activities of daily living is often limited by the ability to generate high mechanical outputs. Therefore, assessing and developing maximal neuromuscular capacity is essential for determining age-related risk for functional decline as well as the effectiveness of therapeutic interventions. Interventions designed to enhance neuromuscular capacities underpinning maximal mechanical outputs could positively impact functional performance in daily life. Unfortunately, < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Muscle action or contraction type is one variable of resistance exercise programming that has received little attention in position papers on resistance exercise guidelines (Table 1 ) and in previous discussions on minimal dose resistance exercise strategies [ 47 ]. A typical repetition of a resistance exercise consists of both an eccentric (i.e., active muscle lengthening) and concentric (i.e., active muscle shortening) muscle action (i.e., a coupled eccentric–concentric repetition).…”
Section: Minimal Doses Of Eccentric Resistance Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Muscle action or contraction type is one variable of resistance exercise programming that has received little attention in position papers on resistance exercise guidelines (Table 1 ) and in previous discussions on minimal dose resistance exercise strategies [ 47 ]. A typical repetition of a resistance exercise consists of both an eccentric (i.e., active muscle lengthening) and concentric (i.e., active muscle shortening) muscle action (i.e., a coupled eccentric–concentric repetition).…”
Section: Minimal Doses Of Eccentric Resistance Exercisementioning
confidence: 99%
“…This suggests a unique role for prescriptions of eccentric resistance exercise for older adults and those with cardiovascular or other medical conditions [ 116 , 117 ], who might benefit from minimal dose training strategies. Nevertheless, we are aware of only one paper that has discussed eccentrics as a potential minimal dose approach [ 47 ].…”
Section: Minimal Doses Of Eccentric Resistance Exercisementioning
confidence: 99%
“…In recent years, resistance or strength training, especially eccentric strength training, has become one of the most effective methods to counteract age-related changes of muscle mass and other structures [ 44 ]. Numerous studies have discussed the several benefits and unique physiological advantages of eccentric training compared to standard resistance training.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have discussed the several benefits and unique physiological advantages of eccentric training compared to standard resistance training. There are probable suggestions that eccentric training is metabolically efficient (lower physiological demand) at a given workload with high work output [ 19 , 44 , 45 ]. Furthermore, some studies reported lower or minimal cardiorespiratory load evoked by eccentric exercise, which could be an advantage when applied for older individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation